Bioconversion of seaweed with white rot fungi for production of protein enriched fish feedstock - Jamal, Parveen; Saheed, Olorunnisola Kola; Jaswir, Irwandi; Ruqayyah, Tijani I.D. (2015)
Viable and economical source of fish feed ingredients remained one of most important factors for a successful and profitable fish production for peasant farmers and large scale producers. The process conditions necessary for solid state bioconversion (SSB) of seaweed for synthesis of protein was explored in this study. Phanerochaete chrysosporium (P. chrysosporium) was cultivated under SSB on seaweed for 7days. Investigation of processing factors individually revealed 70% moisture content, 9% inoculum size and 7% of minerals as optimum for protein synthesis. Optimization of protein synthesis by response surface methodology increased crude protein to 120.29 mg/g. Positive interactions were recorded for all investigated process conditions and the quadratic model describing the process was significant at p<0.05. Validation of the model showed protein production falling within 10% tolerable points.